Fracture networks in shale-hosted igneous intrusions: Processes, distribution and implications for igneous petroleum systems. (September 2021) - Rabbel, Ole; Palma, Octavio; Mair, Karen; Galland, Olivier; Spacapan, Juan B.; Senger, Kim
Abstract: Igneous intrusions in sedimentary basins can influence basin-scale fluid flow and petroleum systems in various ways. They may act as barriers, preferential pathways or even reservoirs for fluids. The fracture networks of intrusions usually represent the main control of their hydraulic properties. However, our understanding of different fracturing mechanisms and their quantitative effect on fracture network properties remains limited, and good field examples are sparse. Here, we present a comprehensive field study from the Neuquén Basin, Argentina, using a reservoir-scale outcrop of a sill complex emplaced in organic-rich shale, which constitutes a direct analogue of oil-producing fractured igneous reservoirs. We provide field evidence of various fracturing mechanisms affecting the fracture network, including cooling joints, bituminous dykes, hydrothermal veins, and tectonic faults. Using high-resolution digital fracture network quantification, we then tie these fracture mechanisms to spatial variations of fracture orientation, intensity and connectivity. Our results indicate that all observed fracture types are involved in hydrocarbon migration and/or storage. Bitumen of very high thermal grade within the intrusions implies migration of hydrocarbons into the sills in a destructive high-temperature environment. Importantly, bitumen dykes and faults locally alter the fracture network, creating zones of strongly increased fracture intensity and connectivity and therefore improved reservoir properties. Highlights: Fractures formed by at least four different mechanisms in studied reservoirs. Different fracturing mechanisms lead to strong spatial fracture network variations. Bitumen dykes and faults increase fracture intensity and connectivity. Fracture lengths are log-normal, not power law. Graphitized bitumen within studied intrusions indicates destruction of hydrocarbons.